The effect of interactions between proteinuria, activity of fibroblast growth factor 23 and serum phosphate on renal progression in patients with chronic kidney disease: a result from the KoreaN cohort study for Outcome in patients With Chronic Kidney Disease study. (4th January 2019) - Kim, Hyoungnae; Park, Jimin; Nam, Ki Heon; Jhee, Jong Hyun; Yun, Hae-Ryong; Park, Jung Tak; Han, Seung Hyeok; Chung, Wookyung; Oh, Kook-Hwan; Park, Sue Kyung; Kim, Soo Wan; Kang, Shin-Wook; et al.
Abstract: Background: Recent experimental study reported that proteinuria increases serum phosphate by decreasing biologic activity of fibroblast growth factor 23 (FGF-23). We examined this relationship in a large chronic kidney disease (CKD) cohort and evaluated the combined effect of proteinuria, FGF-23 activity and serum phosphate on CKD progression. Methods: The activity of FGF-23, measured by the fractional excretion of phosphate (FEP)/FGF-23 ratio, was compared according to the degree of proteinuria in 1909 patients with CKD. Primary outcome was CKD progression defined as ≥50% decline of estimated glomerular filtration rate, doubling of serum creatinine and start of dialysis. Results: There was a negative relationship between 24-h urine protein (24-h UP) and FEP/FGF-23 ratio (γ −0.07; P = 0.005). In addition, after matching variables associated with serum phosphate, patients with more proteinuria had higher serum phosphate (P < 0.001) and FGF-23 (P = 0.012), and lower FEP/FGF-23 ratio (P = 0.007) compared with those with less proteinuria. In the matched cohort, low FEP/FGF-23 ratio was an independent risk factor for CKD progression (hazard ratio 0.87 per 1 log increase; 95% confidence interval 0.79–0.95; P = 0.002), and there was significant interaction between 24-h UP and FEP/FGF-23 ratio (P = 0.039). Furthermore, 24-h UP and serum phosphate also had a significant interaction on CKD progression (P < 0.001). Conclusions: Proteinuria is associated with decreased biologic activity of FGF-23 and increased serum phosphate. Furthermore, diminished activity of FGF23 is an independent risk factor for renal progression in proteinuric CKD patients.